Strategi Pemasaran Dalam Meningkatkan Penjualan Usaha Minuman Teh Poci Pondok Hijau Bekasi - Faizal Bagasasi; Hadita Hadita (Journal of Management and Creative Business, 2024)
Marketing strategy is a way to generate profits or targets. By improving the products the company sells. One of the marketing mix strategies that companies often consider is this strategy. This research aims to find out how marketing tactics contribute to the growth of sales of Poci Pondok Hijau Bekasi tea drinks. This type of research uses a qualitative descriptive method, namely an approach that uses various scientific methods to study the condition of natural objects by describing the forms of words and language in certain natural environments. Primary and secondary data are used as data sources. Data collection methods include interviews, observation, and documentation. After that, methods are used to investigate the data and verify its correctness. These results indicate that the marketing mix and marketing strategy are very important in driving sales of the Teh Poci Pondok Hijau Bekasi beverage business.